1987
DOI: 10.1111/j.1471-4159.1987.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Retention of Vasopressin by Hippocampus Vessels In Vivo, Associated with Inhibition of Blood‐Brain Transfer of Large Neutral Amino Acids

Abstract: Vasopressin receptors have been reported in the endothelium of brain capillaries. The function of these receptors is not known. To test the prediction that vasopressin receptors in brain capillary endothelium affect amino acid transport across the blood-brain barrier and to assess the role of vasopressin transport across the cerebral vascular endothelium, we measured (a) the endothelial permeability to the large neutral amino acid leucine in the absence and presence of arginine vasopressin (AVP) and (b) the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The transporter is nearly saturated and competitors in plasma inhibit the transport of both labeled compounds (Leenders et a!. , 1986b;Gjedde and Bodsch, 1987;Reith et a!. , 1987) .…”
Section: Md(t) + Mm(t) R(t) = M�(t) + M�(t)mentioning
confidence: 99%
“…The transporter is nearly saturated and competitors in plasma inhibit the transport of both labeled compounds (Leenders et a!. , 1986b;Gjedde and Bodsch, 1987;Reith et a!. , 1987) .…”
Section: Md(t) + Mm(t) R(t) = M�(t) + M�(t)mentioning
confidence: 99%
“…Prcvious studies have shown that intracarotid or intravenous administration of VP to rats decrease the transport across the BBB of the LNAAs L-leucine and L-phenylalaninc (Brust, 1986;Reith et al, 1987;Brust and Diemer, 1990). By using a noninvasive technique to study BBB transport of amino acids, we examined thc cffccts of VP on ["Clmethioninc transport into thc brain of adult mongrel dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques, e g , the intravenous injection methods (Baiios ct al., 1975;Gjedde et al, 1980;Mans el al., 1982), do not permit the separate evaluation of the PSproduct ofindividual amino acids (however, see also Gjedde and Bodsch, 1987). Effccts of AVP on BBB amino acid transport were dcmonstrated in rats using both thc carotid injection tcchnique (Brust, 1986;Brust and Zicha, 1988) and the intravenous injection or intcgral method (Reith et al, 1987;Brust and Diemer, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations